APLIKASI ALAT ELEKTRODEKOLORISASI DENGAN ELEKTRODE SENG DAN KARBON BEKAS UNTUK PENGOLAHAN LIMBAH ZAT WARNA HASIL PRAKTIKUM DAN PENELITIAN (STUDI KASUS DI LABORATORIUM TERPADU UIN SUNAN KALIJAGA YOGYAKARTA) - Isni Gustanti; Indra Nafiyanto (UIN Sunan Kalijaga Yogyakarta, 2018)
Integrated Laboratory UIN Sunan Kalijaga outline has three functions, namely as a service practice, research and public service (community service). As a function for practice and research using diverse materials to chemicals, one of which is a synthetic dye. If we observe, sewage waste dye lab work and research results are still stored in tanks of waste and waste have not been processed to become complex dye. Waste dye is then processed by means of elektrodekolorisasi using zinc and carbon electrodes former.Elektrodekolorisasi with zinc and carbon electrodes on the former waste dye lab results and research in the Laboratory of Integrated UIN Sunan Kalijaga, carried on the strong current of 2 A, voltage of 8 volts and 30 seconds. Waste dye in the Integrated Laboratory UIN Sunan Kalijaga can didekolorisasi with elektrodekolorisasi tool uses zinc and carbon electrodes in normal conditions, acidic (pH 2) and the addition of salt. In normal conditions, the percentage of samples elektrodekolorisasi to 1 at 13.09% and the samples to 2 at 14.09%. In acidic conditions (pH 2), the percentage of samples elektrodekolorisasi 3 to 63% and the samples to 4 of 82.25%. On the condition of adding salt (NaCl), the percentage of samples elektrodekolorisasi to 5 at 99.68% and the samples to 6 amounted to 99.60%. Based on the results elektrodekolorisasi, the most optimal conditions the addition of salt in waste mendekolorisasi dye.